Construction of a neonatal cortical surface atlas using multimodal surface matching - Bozek, J; Fitzgibbon, S; Wright, R; Rueckert, D; Jenkinson, M; Robinson, E (IEEE, 2016)
In this paper we propose a method for constructing a spatiotemporal cortical surface atlas of neonatal brains aged between 38 and 42 weeks of gestation at the time of scan. The method is based on a spherical registration approach: multimodal surface matching (MSM) registration, where cortical folding patterns were used to drive alignment. Cortical surfaces from 44 subjects were projected onto spheres and grouped into 5 weeks, with all surfaces within each group co-registered using pairwise MSM registration in order to avoid bias in the atlas towards any of the subjects. Finally, warps were projected to the anatomical surfaces to allow averaging of white matter surfaces, and folding metrics, in the template space. Our approach improves the sharpness of the templates from what can be achieved using affine alignment alone.